Problems of legal protection of civilian persons deprived of personal liberty as a result of the armed aggression of the Russian Federation against Ukraine - Filatov, Viktor; Zuieva, Oksana; Yefimova, Inna; Pylypenko, Anzhelika; Leheza, Yevhen (DIXI, 2024)
The article deals with the issues of legal protection of Ukrainian citizens detained by the aggressor state. The authors focus on civilians, who have a special international legal status in wartime. Three clusters of problems are analyzed separately: issues of national legislation, organizational and structural problems, and issues of international legal acts application. It is emphasized that the presence of these problems inhibits the process of making a special mechanism for identification and return to Ukraine of civilians held by the aggressor state. It is noted that the imperfection of national legislation causes the existence of a number of systemic problems of social and economic, and organizational and legal protection of civilians who are detained and held by the aggressor state. The reasons are given for organizational and structural problems that are mainly related to the absence of a Patron State, which also complicates the process of identification and return of Ukrainian citizens held by the aggressor state. It was established that the key problem of the international legal acts application in the researched area is the declarative nature of the forms of international institutions’ influence that are unable to force the aggressor state to stop violence and systematic violations of human rights. The article offers recommendations for authorities and civil society regarding the development in Ukraine of a special mechanism for the identification and return of civilians held by the aggressor state.
Keywords: Aggressor state; armed aggression; guarantee system; international legal acts; legal status; missing person; national legislation; state policy; temporarily occupied territory